End-User Development 4th International Symposium, IS-EUD 2013, Copenhagen, Denmark, June 10-13, 2013, Proceedings - Dittrich, Yvonne; Burnett, Margaret; Morch, Anders; Redmiles, David (Programming and Software Engineering,, 2013)
This book constitutes the refereed proceedings of the Fourth International Symposium on End-User Development, IS-EUD 2013, held in Copenhagen, Denmark, in June 2013. The 13 full papers (45% acceptance rate) and 11 short papers (50% acceptance rate) have been presented at the event. In addition the volume contains two keynote speeches, three doctoral consortia papers, and information on 2 workshops. The papers provide a broad overview of the current state of End-User Development research.